A critical analysis of Western Civilization and Iqbal’s Philosophy - Arshad Iqbal; Dr. Haris Mubeen (jihat-ul-islam, 2021)
Western civilization refers to the Renaissance and Reformation movements that emerged after the Conquest of Constantinople and engulfed not only Europe but also the United States of America. These movements first gave birth to modernization which gave human rights, liberty, capitalism and communism no less than a religious significance. After the Second World War, postmodernism challenged all the mighty narratives of modernism. Allam Iqbal (1877-1938) was born at a time when Westernization was undergoing modernization. Philosophy and science were not mere ideas rather they had assumed a new trajectory, thanks to modern technology that had an indelible impact on metaphysical beliefs of almost all religions in the world. Since most of Allama Iqbal’s education was based on Western paradigms, he acknowledges its efficacy. But, the way the Western philosophy impacted Muslims’ hearts and minds make him highly critical of it. To counter the Western ideals of society, democracy and human rights, Iqbal presents the concepts of Islamic civilization, spiritual democracy and human rights in the light of the Seerah of the Holy Prophet (SAWW). It is not the case that he prioritized Eastern civilization over the Western one; rather, he also enlightened his nation on the flaws of the former. He, n fact, is an advocate of Islamic civilization, which is depicted by his verse. ا ینپ رپایق وقِمُروس ِل اوقا ہن رک اخصےہ رتبیکںیم اہیمش ِمرغم ب مِ س ےس لّت Judge not your nation on the criteria of Western nations Special in composition is the Hashimi Prophet’s nation.